EVALUASI PENGGUNAAN OBAT ANTITUBERKULOSIS PADA PASIEN TUBERKULOSIS PARU DI INSTALASI RAWAT INAP BLU RSUP PROF. DR. R. D. KANDOU MANADO PERIODE JANUARI – DESEMBER 2010 - Simamora, Vethreeany; Tjitrosantoso, Heedy; Wiyono, Weny (PHARMACON, 2012)
This study aims to examine the patterns of the use of antituberculosis drugs (OAT) and to evaluate thesuitability of the use of OAT based on the Guidelines for Tuberculosis Control 2009 by Ministry ofHealth RI, in hospitalized patients with pulmonary tuberculosis in BLU RSUP Prof. Dr. R. D. KandouManado period January to December 2010. This study is a descriptive survey research and datacollection carried out retrospectively. Data was analyzed with descriptive analysis. The resultsshowed patients with category 1 of an intensive phase is given the alloy HRZE or 4FDC andcontinoum phase patients is given the alloy HR. Category 2 patients, the 2-month intensive phase isgiven the alloy HRZES and for category 2 patients at 1-month intensive phase is given the alloyHRZE. A total of 97.7% of patients prescribed a single drug dosage OAT (generic) and 2.3% ofpatients prescribed OAT FDC. Based on the suitability of the selection of alloys OAT, for thetreatment of category 1 have met the suitability of 94.7% and category 2 is 66.7%, compliance withthe standards of the Guidelines for Tuberculosis Control 2009 by Ministry of Health RI.Keywords: OAT, pulmonary tuberculosis, hospitalized patients